Retinal Structure in RPE65 -Associated Retinal Dystrophy - Kumaran, Neruban; Georgiou, Michalis; Bainbridge, James W. B.; Bertelsen, Mette; Larsen, Michael; Blanco-Kelly, Fiona; Ayuso, Carmen; Tran, Hoai Viet; Munier, Francis L.; Kalitzeos, Angelos; Michaelides, Michel (Investigative ophthalmology & visual science, 2020)
RPE65-associated retinal dystrophy (RPE65-RD) is an early onset, progressive, severe retinal dystrophy. We sought to characterize the natural history of retinal degeneration in affected individuals. We performed cross-sectional and longitudinal quantitative and qualitative assessments of retinal architecture in RPE65-RD using spectral domain optical coherence tomography (SD-OCT) and fundus autofluorescence (FAF) imaging. Twenty-six subjects (mean age, 14.8 years, range, 5-24 years) with RPE65-RD underwent SD-OCT and FAF imaging, of whom 14 subjects were followed up over time. Foveal thickness (FT), outer nuclear layer thickness (ONLT), ellipsoid zone width (EZW), and ellipsoid zone area (EZA) were calculated where possible. These were correlated with age, best corrected visual acuity (BCVA), and central 30° retinal sensitivity (V30). Intra-observer agreement, test-retest repeatability, and interocular symmetry were also investigated. We identified structural interocular symmetry, the presence of autofluorescence in 46% (12/26) of subjects, and the presence of foveal hypoplasia (associated with significantly worse BCVA) in 50% of subjects. EZW and EZA were measurable in 67% (35/52) and 37% (19/52) of eyes, respectively, with both demonstrating good agreement on repeated measurement. The annual rate of progression using EZW was -300.63 µm/year, and -1.17 mm2/year in EZA. EZW was found to have a statistically significant correlation with BCVA and V30. We identified the presence of autofluorescence in half of our subjects, with foveal hypoplasia also noted in half of our cohort. EZW, and to a lesser extent EZA, were robust measures of retinal degeneration and represent valuable metrics to determine the impact of intervention. (ClinicalTrials.gov number NCT02714816.).